Safety and Predictors of Sexual Minority Youth Carrying Weapons. Issue 11 (June 2022) - Streed, Carl G.; Turner, Blair; Beach, Lauren B.; Marro, Rachel; Felt, Dylan; Wang, Xinzi; Phillips, Gregory
Prior research has revealed sexual minority youth are more likely to carry weapons both outside of and within school. However, to date, no study has examined the degree to which bullying and harassment is associated with weapon carrying among sexual minority youth. We utilized the Youth Risk Behavior Survey to examine the prevalence and likelihood of carrying weapons by sexual identity, adjusting for adverse experiences. From the Youth Risk Behavior Survey 2009-2015, we examined self-report of adverse experiences (e.g., being bullied, skipping school due to fear for personal safety) and performed Logistic regressions to estimate the odds of carrying a weapon and were adjusted to include demographics and adverse experiences. When surveyed by sexual identity, 14.0% of heterosexual, 21.8% of gay/lesbian, 18.5% of bisexual, and 17.4% of "not sure" students reported carrying a weapon in the past 30 days. Odds of carrying a weapon were significantly increased for youth who skipped school due to feeling unsafe at school, had ever been threatened with a weapon in the past year, and had ever been in a physical fight. Compared to heterosexual female peers, sexual minority women had increased odds of carrying a weapon. Pediatricians should recognize that experiencing bullying and feeling unsafe are associated with weapon carrying, particularly among sexual minorities. Pediatricians and professionals who work with youth should recognize that reported experiences of bullying may not be the most salient indicator of risk for weapon carrying among all youth, and that other fears of or experiences with bullying are crucial to screen for among sexual minorities in particular.